Mexico: the strategy to achieve sustained economic growth - Loser, Claudio ed (I.M.F. Washington, D.C.US, 1992)
Reviews central aspects of the Mexican economy over the last decade. Discusses macroeconomic policies and analyses the evolution of structural reforms in key areas viz. financial systems, trade and foreign investment. Also considers dynamics of inflation, balance of payments and other key variables.